Strategi Lembaga Pendidikan MA’ARIF NU Pusat Dalam Menghadapi Tantangan Di Era Globalisasi - Nur Afif; M Azmi Zamzami; Asrori Mukhtarom; Agus Nur Qowim (Universitas Muhammadiyah Tangerang, 2022)
This study aimed to determine the strategy of NU ma'arif educational institutions in facing challenges in the era of globalization. The research design is a field study approach (field research). The results of the study show that Ma'arif NU Center has three perspectives in viewing globalization and its challenges, namely: 1) globalization as a new challenge 2) globalization as an opportunity for new discoveries 3) globalization as a threat to cultural identity. The strategies undertaken by LP Ma'arif NU Center in facing challenges in the era of globalization are 1) facilitating the needs of educational units to innovate 2) consistently developing human resources 3) improving the quality of facilities and infrastructure 4) strengthening cultural identity 5) increasing collaboration Keywords: Globalization, Strategy, and LP Ma'arif NU